CP-132 Facing the challenge of off-licence drug administration in patients with dysphagia. (24th February 2014) - Schartmueller, H; Jouët-Pastré, A; Haider, D
Abstract : Background: A clinical pharmacy service is provided to a 192 bed nursing care home for the elderly on a hospital site in Vienna, Austria. In total 28% of residents have dysphagia and need their oral medicines reformulated prior to administration. Purpose: To raise nurses' awareness of the issues related to these off-license methods of drug administration and to minimise associated risks. Materials and methods: A presentation was given for nurses on drug administration to patients with dysphagia. After the presentation a non-disguised questionnaire consisting of 16 questions was used. Fourteen closed-ended questions, one open-ended question and one question using a rating scale from one to five were asked. The data obtained were analysed quantitatively. A specially designed form and the drug charts were used to collect data on residents with dysphagia. A pharmacist evaluated the appropriateness of the methods used to present the prescribed medicines based on most up-to-date evidence. Administration and prescribing advice were given through a pharmacy medication check service to health care professionals (HCPs). Results: A total of 54 HCPs attended the presentation and 50 questionnaires were returned resulting in a response rate of 93%. 84% of these HCPs administer drugs and for 80% it was a relevant topic. Two third of HCPs need 1–3 h daily for drug administration to dysphagia patients. The majority of answers showed that risks such as cross contamination, treatment failure and adverse drug reactions due to pharmacokinetic changes were identified in current clinical practice. Specific administration advice for HCPs was given for 148 of 443 (33%) prescribed medicines. 26 medicines had to be changed to an alternative and for 13 medicines a more appropriate formulation was recommended. Conclusions: This project shows that there was need to improve the drug management of patients with dysphagia. The HCPs welcomed the presentation on this topic and the introduction of a pharmacy medication check service to support them with administration advice and to minimise risk for patients. No conflict of interest.